Clinical evaluation of air polishing with erythritol powder followed by ultrasonic calculus removal versus conventional ultrasonic debridement and rubber cup polishing for the treatment of gingivitis: A split‐mouth randomized controlled clinical trial. Issue 2 (28th July 2021) - Mensi, Magda; Scotti, Eleonora; Sordillo, Annamaria; Dalè, Matteo; Calza, Stefano
Abstract: Objectives: To evaluate the clinical efficacy in the short‐term resolution of gingivitis of a novel protocol involving full‐mouth erythritol powder air polishing followed by ultrasonic calculus removal. Methods: Forty‐one healthy patients completed the study. Following a split‐mouth design, quadrants 1–4 and 2–3 were randomly allocated to receive air polishing followed by ultrasonic calculus removal (A+US) or traditional full‐mouth ultrasonic debridement followed by polishing with a rubber cup and prophylactic paste (US+P). Bleeding on probing (BoP) and plaque index (PI) were collected at baseline and 2 and 4 weeks. Moreover, the residual plaque area (RPA), treatment time and patient comfort/satisfaction were evaluated at the end of the treatment. Results: Both treatments showed a significant reduction in BoP and PI. At 4 weeks, A+US seems to reach a statistically significant lower BoP (8.7% [6.9; 10.9] vs. 11.6%[9.3; 14.4], p  < 0.0001) and PI (10.7% [8.9; 13.0] vs. 12.3% [10.2; 14.9], p  = 0.033). Moreover, A+US treatment time lasted on average 9.2% less than US+P ( p  < 0.0001) and was the preferred treatment for a significantly higher number of patients (73.2% vs. 17.1%, p  = 0.0001). Conclusion: The A+US protocol is suitable for the short‐term resolution of plaque‐induced gingivitis.